Game theory and governance of protected areas – Peneda-Gerês National Park - Sónia Nogueira; Shital Jayantilal; Sílvia Ferreira Jorge; Diogo Lourenço (Cogent Business & Management, 2023)
The literature shows that integrating tourism management with place governance practices is conducive to harmony and development in urban areas. However, protected areas face peculiar governance and management challenges. This article offers an in-depth study of the governance of the Peneda-Gerês National Park in Portugal. We model the incentive structure of some of its stakeholders through game theoretical techniques and find that early phases were not conducive to cooperation among relevant stakeholders, potentially leading to outcomes that were less than optimal, both to them and to the park. The most recent, co-management, model seems much more promising.
Keywords: 650; Game theory; place governance; stakeholders theory; strategy; tourism